The Impact of Teachers’ Pedagogy on English Oral Communication Skills of Grade 5th Students (Journal of Contemporary and Applied Social Sciences, 2026)
The main objective of this study was to investigate how different pedagogical strategies adopted by teachers impact the ability of Grade 5 students in government public schools to speak and listen to English effectively. The experiment used to involve a true experiment approach with the participation of 60 subjects selected from three public government schools. The Topics were allocated to the experimental group (n=30) and control group (n=30). Pre-tests were carried out on 4, 5, and 6 May 2026 to determine the oral communication skills of the students before the intervention process. The experimental group was taught using an instructional approach for four weeks that incorporated interactive teaching strategies such as storytelling, role plays, question and answer sessions and working in pairs, while the control group was instructed using a traditional teaching method. Final examinations were then performed on 1, 2, and 3 June 2026. The results show that the experimental group implemented significantly better than the control group in English oral communication. The mean scores of the experimental group increased from 37.50 during the pre-test to 43.17 after the final examinations, while those of the control group increase in numbers a little from 35.53 to 37.37. The results show that effective and learner-centered pedagogical approaches significantly increase the ability of learners to communicate both orally and through listening. As per the findings, it can be said that an effective methodology will be required for the development of the communication skills of the children using spoken English. This implies that the teacher should use general education methods that will ensure an active teaching atmosphere and develop the language proficiency of the learners